Islande = Islanda = Island = Iceland : 1:500,000 / Freytag & Berndt (Freytag, Berndt und Artaria, 2003)
Relief shown by shading and spot heights.; Legend and panel title in English, German, French, and Italian.; Panel title.; Includes col. ill.; "Laufzeit: 10/2003 2070/1109". Originally folded to 24 x 13 cm. Color 1:500,000